Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.13102/sociobiology.v65i2.2742
|View full text |Cite
|
Sign up to set email alerts
|

Ants that Frequently Colonize Twigs in the Leaf Litter of Different Vegetation Habitats

Abstract: Ants often colonize twigs in the leaf litter, but some species use this resource more frequently than others. We analyzed the composition of the community and the diameter of colonized twigs to test if any species had a size preference. Samples were collected in different vegetation habitats (urban parks, eucalyptus plantations and native forests). In each site, all twigs with an ant colony in six 16-m2 plots were collected and measured, and the ants occupying them were identified. For the analyses, we only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…(Table 1). All these species are considered common inhabitants of twigs, because they are ant that colonized 10 or more twigs in a given leaf litter area (Fernandes et al 2018). Our results show also that P. sarcina is the species that most uses twigs in the leaf litter as a resource, which corroborates the results of Fernandes et al (2018).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…(Table 1). All these species are considered common inhabitants of twigs, because they are ant that colonized 10 or more twigs in a given leaf litter area (Fernandes et al 2018). Our results show also that P. sarcina is the species that most uses twigs in the leaf litter as a resource, which corroborates the results of Fernandes et al (2018).…”
Section: Resultssupporting
confidence: 85%
“…occupies twigs with the largest diameter, but in less proportion. Possibly P. sarcina is the most generalist in the twig occupation, which corroborates the results found by Fernandes et al (2018). These authors have shown that this species occupies most of the twigs in Atlantic forest areas.…”
Section: Speciessupporting
confidence: 90%
See 1 more Smart Citation
“…Decision-making in ants often involves nest-site selection (Pratt & Pierce, 2001), but we cannot conclude that all species in the same genus occupied the same type of nest, since only 3 (27%) out of 11 Pheidole species were found in twigs that shared the same areas and twig hole circumferences. Of these, P. sospes also showed preference for twig diameter, regardless of habitat (Fernandes, Souza-Campana, Silva, & Morini, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Souza-Campana et al (2017) showed that diameter explained the richness of ant communities in twigs. Some species even colonize same-diameter twigs, regardless of habitat (Fernandes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%